The Concept of Law: A New Methodological Approach to Robert Alexy's Theory - Gaido, Paula (2021)
In this paper I try to make clear R. Alexy's idea when he says that the purpose of the philosophy of law is to give an explanation of the nature of law. In this context the question about the nature of law is a question about its essential properties, that is, about its necessary properties. To identify how the idea of necessity is understood is thus central. Alexy uses this expression ambiguously, and that impacts his use of the expression «concept of law», which is also ambiguous. I suggest that he uses the expression the «concept of law» in. two different senses, and maintain that if that is taken into account, we could better identify which is the theoretical enterprise with which Alexy is really committed. Finally, I notice a further contradiction in his argument when he affirms that the nature of law can be captured only from the perspective of the participants of the legal practice.